The relationship between pressure offloading and ischial tissue health in individuals with spinal cord injury: An exploratory study. (30th September 2019) - Gabison, Sharon; Mathur, Sunita; Nussbaum, Ethne L.; Popovic, Milos R.; Verrier, Mary C.
Abstract : Objectives: To compare thickness and texture measures of tissue overlying the ischial region in able-bodied (AB) individuals vs. individuals with spinal cord injury (SCI) and to determine if there is a relationship between pressure offloading of the ischial tuberosities (IT) and tissue health in individuals with SCI. Design: Exploratory cross-sectional study. Setting: University setting and rehabilitation hospital. Outcome Measures: Thickness and texture measurements from ultrasound images of tissues overlying the IT were obtained from AB individuals ( n = 10) and individuals with complete or incomplete traumatic and non-traumatic SCI American Spinal Injury Association Impairment Scale (AIS) classification A–D ( n = 15). Pressure offloading was measured in individuals with SCI and correlated with tissue health measurements. Results: The area overlying the IT occupied by the muscle was significantly greater in the SCI when compared with AB cohort. The area occupied by the muscle in individuals with SCI appeared to lose the striated appearance and was more echogenic than nearby skin and subcutaneous tissue (ST). There was no correlation between offloading times and thickness, echogenicity and contrast measurements of skin, ST and muscle in individuals with SCI. Conclusion: Changes in soft tissues overlying the ischial tuberosity occur following SCI corresponding to the loss of striated appearance of muscle and increased thickness of the area occupied by the muscle. Further studies using a larger sample size are recommended to establish if thickness and tissue texture differ between individuals with SCI who sustain pressure injuries vs. those who do not.